Opoziční smlouvy „za kopečky“ II.: Byl pakt ČSSD a ODS z let 1998-2002 demokratickou deviací? - Kopeček, Lubomír (Středo Evropské politické studie, 2013)
This is the second part of a two–part paper, the first one having been published in the previous volume of this journal. After the 1998 general elections to the Chamber of Deputies of the Czech Republic, the largest party, the Social Democratic Party (ČSSD), formed a minority government. The origin and existence of this government was enabled by an agreement with the second largest formation, the Civic Democratic Party (ODS). What was then known as the Opposition Agreement became the subject of considerable debate. The first part of the paper provided analysis of government practice in similar circumstances in Denmark, Sweden, New Zealand, and Italy at the time of the Historic Compromise. Here I focus specifically on the Czech case. The present paper points out not only the Opposition Agreement between the Social Democrats and the Civic Democratic Party and the later Toleration Patent, which even deepened the cooperation between these two parties, but also the frequent ad hoc legislative coalitions which the minority government was able to form.